The impact of an urbanizing tropical watershed to the surface -runoff - B.S. Igulu; E.E. Mshiu (Global Journal of Environmental Science and Management)
The lack of hydrological data for urbanizing watersheds in developing countries is one of the challenges facing decision making. Msimbazi River is located in the city center of Dar es Salaam and is highly influenced by human activities; this includes dense populations that are characterized by informal settlements. The catchment is currently undergoing flooding, which triggers a dilemma in its surface runoff trending. This study aimed to simulate rainfall-runoff of an urbanizing Msimbazi watershed that will provide an understanding of hydrological data including peak flows and discharge volumes of Msimbazi River. The data used in the study include soil, rainfall, DEM and land use. HEC-GeoHMS and ArchHydro tools in ArcGIS were used to generate hydrological inputs to be used in the HEC-HMS interface. The resulted sub-watersheds have high CN values ranging from 70 to 90 implying the possibility of high runoff potential. Sub-watershed W620 indicates the highest runoff, among others with the highest runoff of 290mm for the year 2015. The peak flow on the river indicates the value ranging from 7.2 m3/s to 30m3/s with the highest values being on the downstream. The overall trend indicates an increasing surface runoff and peak flow in sub-watersheds from 1985 to 2015. Simulated results in this study were validated with the observational data of the catchment recorded in 2017. Given that most of the rivers in Tanzania are ungauged, the approach applied in this study can be used to enhance decision making on settlement planning, water resource, and disaster management in the currently observed urbanizing areas.